Analisis Kontribusi Sektor Perekonomian Tehadap PDRB di Kota Banjarmasin dan Komparasi Dengan Kota Banjarbaru Tahun 2016-2020 - Salbiah, Siti; Chandriyanti, Ika (PPJP Universitas Lambung Mangkurat, 2023)
This study was conducted to determine the economic sector's contribution to Banjarmasin's GRDP from 2016 to 2020 and to compare it to the town of Banjarbaru. The types of research used in this research are descriptive and comparative. The data analysis technique used in this study is a descriptive method with a contribution approach. The analysis results show that the manufacturing sector makes the highest contribution to forming the GRDP of Banjarmasin City. The average contribution of the processing industry from 2016 to 2020 is 17,89%. Based on the results of the sector analysis, the first and most significant contribution to the formation of the GRDP of Banjarbaru from 2016 to 2020 is the transportation and warehousing sector, with an average of 19,46%.